Processo de preparação de obras de câmara pelo quarteto Corda Nova: uma abordagem etnográfica. - Marcos Matturro Foschiera (2015)
This thesis aims to analyze musical strategies and social and cultural relations that permeate and impact the process of preparing a repertoire for performance through observation, analysis and reporting of different rehearsals and presentations of Corda Nova guitar quartet (Belo Horizonte - MG), which is dedicated to contemporary music. The methodology used in data collection was the ethnographic approach, which includes three steps: 1) in person observations, audiovisual recording for registration and analysis of several trials group; 2) observation, audiovisual recording for registration and analysis of 2 (two) live performances; and 3) semi-structured interviews with each member separately, in order to understand the different views and perspectives of collective work. From that material collected it was possible to analyze the group's work from two perspectives. The first was detailed collaborative process of quartet members, which were found several specificities of quartet work as rehearsal strategies, roles of members and forms of production of their shows. In the second analyzed the term "sound images", which is used by the group to describe the process of apprehension of musical content, and concluded that the creation of "sound images" of works is built from multiple aspects, such as creating hearing references, rhythms and melodies resultant, personal markings in the score, among others.